Adverse drug reactions in neonates: a brief analysis of the FDA adverse event reporting system - Byskov, Pernille Kähler; Baden, Christoffer Storm; Andersen, Jon Trærup; Jimenez-Solem, Espen; Olsen, Ramus Huan; Gade, Christina; Lausten-Thomsen, Ulrik (Frontiers in Pharmacology, 2024)
Introduction Drug trials in neonates are scarce, and the neonates may consequently be at risk of adverse drug reactions (ADRs). Spontaneous ADR reporting is an important tool for expanding the knowledge on drug safety in neonates. This study explores the quality of current neonatal ADR reports and the ADR reports of the most common drugs used in neonatal departments. Methods An observational cross-sectional study focused on neonates was conducted using data on spontaneous reports extracted from the U.S. Food and Drug Administration Adverse Events Reporting System (FAERS) from the third quarter of 2014 up to December 2022. Only the primary suspect drugs given to neonates or subjects aged <30 days were included in the analysis. Results Spontaneous reports from 13 million patients of all ages, totaling 50 million ADRs, were evaluated. Information regarding the age was missing in 40% of the reports, and data on 43,737 neonates with 948 different suspected drugs were identified and included in the analysis. We report the frequency of spontaneous ADR reports in the FAERS database for the ten most frequently administered drugs in neonatal intensive care units in the USA. Conclusion Overall, neonatal ADRs are still underreported. The FAERS database in its current form discriminates insufficiently between prenatal and postnatal drug exposures. Hence, improved neonatal pharmacovigilance systems are urgently needed.